Efficacy of workplace interventions for shoulder pain: A systematic review and meta-analysis - Veronique Lowry; Ariel Desjardins-Charbonneau; Jean-Sébastien Roy; Clermont E. Dionne; Pierre Frémont; Joy C. MacDermid; François Desmeules (Medical Journals Sweden, 2017)
Objective: To perform a systematic review and meta-analysis of randomized controlled trials on the efficacy of workplace-based interventions to prevent or treat shoulder pain. Data sources: A systematic review of 4 databases was performed up to January 2016. Study selection: Randomized controlled trials were included if the intervention under study was a workplace-based intervention performed to prevent or reduce shoulder pain and disability in workers. Data extraction: The methodological quality of the studies was evaluated and meta-analyses were conducted. Pooled mean differences and risk ratios were calculated. Data synthesis: Data from 4 studies on strengthening exercises performed in the workplace for workers with shoulder pain (n = 368) were pooled. A statistically significant reduction in pain intensity was observed compared with different control interventions (mean differences (scale out of 10) 1.31 (95% confidence interval (95% CI) 0.86-1.76)). Pooled data from 5 studies on the efficacy of workstation modifications (n = 2,148) showed a statistically significant reduction in the prevalence of shoulder pain with a risk ratio of 1.88 (95% CI 1.20-2.96) compared with different control interventions. Conclusion: Low-grade evidence exists that a workplace exercise programme may reduce the intensity of shoulder pain, and that workstation modifications may reduce the prevalence of shoulder pain.